Merger and acquisition in the banking sector - Anna Szewczyk (Contemporary Economics, 2008)
The article presents situation on mergers and acquisitions (M&A) in banking sector during last twenty years. The main motives are selected and analyzed. All is explained on the base on research reports of the Deutsche Bundesbank and the European Central Bank.
Keywords: 330